PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN KINERJA GURU DI SMK MULTI MEKANIK MASMUR PEKANBARU - Muhammad Febrian; Ilham Wahyudi (STKIP Pesisir Selatan, 2026)
This study examines the role of the principal as asupervisor in improving teacher performance and identifies the factors that support and hinder the implementation of supervision at SMK Multi Mekanik Masmur in Pekanbaru. This study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Informants in this study included the school principal, vice principal, and teachers. The results indicate that the school principal carries out supervisory functions through several activities, such as classroom supervision, monitoring instructional materials, providing professional development for teachers, and offering feedback on the learning process. The school principal also serves as an educator, manager, administrator, innovator, and motivator in efforts to improve the quality of teacher performance. In practice, supervision helps teachers improve their teaching methods, mastery of subject matter, and classroom management, as well as enhance their professional responsibility in learning activities. Factors supporting supervision include effective communication, cooperation between school leaders and teachers, and the availability of motivation and opportunities for professional development, such as training and subject-specific teacher working groups (MGMP). Meanwhile, inhibiting factors include limited facilities and infrastructure, the continued presence of contract teachers with inconsistent performance, a lack of discipline among some teachers.